Brand Equity at The Islamic Boarding School (Study The Marketing of Educational Services at Islamic Boarding School in Banjarbaru City) - Adi Ansari; Suraijiah Suraijiah (Management of Education: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to identify and describe brand equity which consists of four assets namely brand awareness, brand association, perceived quality, and brand loyalty at the Al-Falah and Darul Ilmi Islamic boarding schools for girls in the city of Banjarbaru. This research is a type of field research. This study uses a descriptive research method with a qualitative approach. The subjects of this study were potential customers at the Al-Falah and Darul Ilmi Islamic boarding schools for girls. Data collection techniques are observations, interviews, and documentation. Data analysis by data reduction, data presentation, and verification. The results showed that brand awareness at the Al-Falah and Darul Ilmi Islamic boarding schools for girls was at the top of brand level brand association both also show positive information that is supported by positive responses from potential internal customers, supported by the advantages of Islamic boarding schools, suitability for lifestyle/life needs, and suitable prices. Perceived quality both of them show expectations or are satisfied with the quality provided by the Islamic boarding school. Both brand loyalty is at the committed buyer level.